Variability of CPT and tropopause characteristics over the Arabian Peninsula - DALABEEH, FALAHAL (MAUSAM, 2022)
. The climatology of the cold-point tropopause (CPT) and tropopause characteristics in a subtropical area like The Arabian Peninsula is examined using the radiosonde data of the CPT characteristics and NCEP Reanalysis data of the tropopause characteristics. The monthly mean data for January and July are analyzed for three stations, namely Medina, Tabuk and Dammam in Saudi Arabia. The trends of CPT and tropopause characteristics of pressure, height, temperature, temperature anomalies, relative humidity, wind speed and potential temperature are also analyzed. The trends of these characteristics show that they experienced a sharp change during the 1990s and a significant change for the period from 2000 to 2016. For the whole period of study, the month of July, CPT and tropopause pressure decreased for about 5 hPa, whereas the height increased for more than 100 m. The temperature experienced a sudden drop during the beginning of the 1990s and a smooth decrease during the following years in January. Furthermore, a strong correlation is found between the CPT temperature and the Solar Cycle during the ‘90s period then it decreased sharply after this period.